Asian-Pacific Economic Literature. (National Centre for Development Studies for the Economics Division of the Research School of Pacific Studies, ANU, 1987)
It contains policy issues, literature surveys, book reviews, annotated list of books, abstracts of journal articles and papers of selected institutes about all aspects of economic development in the Asia-Pacific region, defined as the developing countries of East Asia and the Pacific islands.